2018
DOI: 10.3389/fpls.2018.01650
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Mutants Related to the C4 Photosynthetic Kranz Structure in Foxtail Millet

Abstract: C4 plants exhibit significantly higher photosynthetic, water and nutrient use efficiency compared with C3 plants. Kranz anatomy is associated with many C4 plants in which bundle sheath cells surround the veins and are themselves surrounded by mesophyll cells. This specialized Kranz anatomy is elucidated as an important contributor to C4 photosynthetic activities in C4 plant. Characterizing the molecular basis of Kranz structure formation has become a key objective for studies of C4 photosynthesis. However, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…2002; Luo et al, 2018;Döring et al, 2019). Knowledge obtained from mutant screenings can reveal new chloroplast functions, including those necessary for high photosynthetic performance, and accelerate the molecular characterization required for deciphering the genetic basis of plant photosynthesis for future improvements.…”
Section: Genomics To Study the Natural Variation Of Plant Photosynthementioning
confidence: 99%
See 2 more Smart Citations
“…2002; Luo et al, 2018;Döring et al, 2019). Knowledge obtained from mutant screenings can reveal new chloroplast functions, including those necessary for high photosynthetic performance, and accelerate the molecular characterization required for deciphering the genetic basis of plant photosynthesis for future improvements.…”
Section: Genomics To Study the Natural Variation Of Plant Photosynthementioning
confidence: 99%
“…The functional dissection of photosynthesis can be undertaken also by forward genetic screens. Strategies, identification, insights and mutant effects have been reviewed previously ( Somerville, 1986 ; Parinov and Sundaresan, 2000 ; Page and Grossniklaus, 2002 ; Luo et al, 2018 ; Döring et al, 2019 ). Knowledge obtained from mutant screenings can reveal new chloroplast functions, including those necessary for high photosynthetic performance, and accelerate the molecular characterization required for deciphering the genetic basis of plant photosynthesis for future improvements.…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistant starch content is another important trait specific to millet grain that awaits scientific intervention to unravel its genetics and genomics [ 45 ]. Other prospective areas of research in millets as compared to major cereals include C 4 photosynthetic traits [ 46 , 47 ] and tolerance to multiple environmental stresses [ 48 , 49 ], the development and characterization of male sterility systems [ 33 , 50 ], enhancing the shelf-life (rancidity issues) [ 51 ], reducing grain antinutrients including phytates, phenols, tannins, and enzyme inhibitors [ 52. , 53.…”
Section: Mainstreaming Millets For Ensuring Multiple Securities Durinmentioning
confidence: 99%
“…Resistant starch content is another important trait specific to millet grain that awaits scientific intervention to unravel its genetics and genomics [45]. Other prospective areas of research in millets as compared to major cereals include C 4 photosynthetic traits [46,47] and tolerance to multiple environmental stresses [48,49], the development and characterization of male sterility systems [33,50], enhancing the shelf-life (rancidity issues) [51], reducing grain antinutrients including phytates, phenols, tannins, and enzyme inhibitors [52][53][54], and addressing the issues of lodging and seed-shattering [43,55]. A recent study also reported an increased incidence of insect pests, wherein up to 150 different species were found to attack millets at different growth and developmental stages [31].…”
Section: Recent Progress In Millet Researchmentioning
confidence: 99%